Signposting the inferencing route: a relevance theoretic analysis of intertextuality and metaphors in print advertisements - Conradie, Marthinus (University of the Free State, 2013)
This article reports an analysis of the manner in which copywriters use direct and indirect product claims to guide consumers’ interpretations of metaphors in print advertisements. The analysis utilises a relevance theoretic framework, and the results are illustrated by means of a qualitative analysis of four case studies, taken from a larger sample of 120 print advertisements. The first stage of the analysis employs the concept ‘intertextuality’ to study the manner in which advertising texts construct the intertext as the source of a metaphor, with the advertised product as the target. In the second stage, a relevance theoretic framework is used to investigate the role that direct and indirect claims play in guiding consumers’ interpretations of the product claims inherent in these metaphors. To achieve the latter aim, Simpson’s (2001) ‘reason’ and ‘tickle’ constructs are used.

Die artikel doen verslag oor ’n ontleding van die wyse waarop kopieskrywers gebruik maak van direkte en indirekte produkaansprake om verbruikers se interpretasies van metafore in gedrukte advertensies te lei. Die analise maak gebruik van ’n relevansie teoretiese raamwerk, en die resultate word geïllustreer deur middel van ’n kwalitatiewe ontleding van vier gevallestudies, geneem uit ’n groter steekproef van 120 gedrukte advertensies. Die eerste fase van die analise maak gebruik van die begrip ‘intertekstualiteit’, ten einde ’n studie te maak van die wyse waarop die interteks opgestel geword as die bron van die metafoor, met die geadverteerde produk as die teiken. Tydens die tweede fase, word ’n relevansie teoretiese raamwerk gebruik om te ontleed watter rol direkte en indirekte aansprake speel in die begeleiding van verbruikers se interpretasies van sulke metafore. Om hierdie doel te bereik, word Simpson (2001) se ‘rede’ en ‘prikkel’ konstrukte gebruik
Keywords: Advertising; Intertextuality; Consumers